Регіональна система медичного обслуговування: сучасний стан і особливості функціонування (на прикладі Сумської області) = Regional health care system: current status and features of the functioning (for example of Sumy region) - Shyschuk, V. D.; Kornus, O. G.; Kornus, A. A.; Shyschuk, A. V. (Journal of Education, Health and Sport, 2015)
Shyschuk V. D., Kornus O. G., Kornus A. A., Shyschuk A. V. Регіональна система медичного обслуговування: сучасний стан і особливості функціонування (на прикладі Сумської області) = Regional health care system: current status and features of the functioning (for example of Sumy region). Journal of Education, Health and Sport. 2015;5(8):126-136. ISSN 2391-8306. DOI 10.5281/zenodo.27738 http://dx.doi.org/10.5281/zenodo.27738 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%288%29%3A126-136 https://pbn.nauka.gov.pl/works/606468 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.06.2015. Revised 15.07.2015. Accepted: 25.07.2015. УДК 614.2:911.3 (477.52) РЕГІОНАЛЬНА СИСТЕМА МЕДИЧНОГО ОБСЛУГОВУВАННЯ: СУЧАСНИЙ СТАН І ОСОБЛИВОСТІ ФУНКЦІОНУВАННЯ (НА ПРИКЛАДІ СУМСЬКОЇ ОБЛАСТІ) REGIONAL HEALTH CARE SYSTEM: CURRENT STATUS AND FEATURES OF THE FUNCTIONING (FOR EXAMPLE OF SUMY REGION) В. Д. Шищук 1,О. Г. Корнус 2, А. О. Корнус 2, А. В. Шищук 1 V. D. Shyschuk, O. G. Kornus, A. A. Kornus, A. V. Shyschuk 1 Сумський державний університет, медичний інститут, м. Суми 2 Сумський державний педагогічний університет, м. Суми, 1Medical Institute of Sumy State University, Ukraine Department of Orthopedics and Traumatology Sanatorna Street 31, Sumy, 40018 2Sumy State Pedagogical University named after A.S. Makarenko, Ukraine Department of general and regional geography Romenska Street 87, Sumy, 40002 e-mail: a_kornus@ukr.net Summary The article is deals the analysis of territorial structure of the health system ofSumyregion. Was considered the current structure of the network of medical institutions and the regularities of their spatial distribution. The provision of population by medical personnel was also characterized. In the article are describes the functional and componential structure of health facilities, involved in various stages of care. The five-taxonomy systematic of settlements, where are the medical facilities of various ranks was proposed. Created the cartographic model of territorial organization of the health system in theSumyregion. Keywords: health care system, territorial organization, stages of care, the ranks of medical centers, a network of hospitals. Резюме У статті розглянуто територіальну структуру системи охорони здоров’я населення Сумської області. Проаналізовано сучасний склад мережі медичних закладів та встановлено закономірності їх просторового розміщення. Охарактеризовано забезпеченість населення медичними кадрами. Описано функціональну та компонентну структуру закладів системи охорони здоров’я, що задіяні на різних етапах надання медичної допомоги. Запропонована п’ятиступенева систематика населених пунктів, де розташовані заклади медичного обслуговування різних рангів. Створено картографічну модель територіальної організації системи охорони здоров’я населення Сумської області. Ключові слова: система охорони здоров’я, територіальна організація, етапи надання медичної допомоги, ранги медичних центрів, мережа лікарняних закладів. Резюме РЕГИОНАЛЬНАЯ СИСТЕМА МЕДИЦИНСКОГО ОБСЛУЖИВАНИЯ: СОВРЕМЕННОЕ СОСТОЯНИЕ И ОСОБЕННОСТИ ФУНКЦИОНИРОВАНИЯ (НА ПРИМЕРЕ СУМСКОЙ ОБЛАСТИ). В статье рассмотрено территориальную структуру системы здравоохранения Сумской области. Проанализирован современный состав сети медицинских учреждений и установлены закономерности их пространственного размещения. Охарактеризована обеспеченность населения медицинскими кадрами. Описаны функциональная и компонентная структура учреждений системы здравоохранения, задействованных на различных этапах оказания медицинской помощи. Предложенная пятиступенчатая систематика населенных пунктов, где расположены медицинские учреждения различных рангов. Создана картографическая модель территориальной организации системы здравоохранения в Сумской области. Ключевые слова: система здравоохранения, территориальная организация, этапы оказания медицинской помощи, ранги медицинских центров, сеть лечебных учреждений.